2013
DOI: 10.1371/journal.pone.0075657
|View full text |Cite
|
Sign up to set email alerts
|

Do Basal Ganglia Amplify Willed Action by Stochastic Resonance? A Model

Abstract: Basal ganglia are usually attributed a role in facilitating willed action, which is found to be impaired in Parkinson's disease, a pathology of basal ganglia. We hypothesize that basal ganglia possess the machinery to amplify will signals, presumably weak, by stochastic resonance. Recently we proposed a computational model of Parkinsonian reaching, in which the contributions from basal ganglia aid the motor cortex in learning to reach. The model was cast in reinforcement learning framework. We now show that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 66 publications
(108 reference statements)
0
7
0
Order By: Relevance
“…Briefly, SR counter-intuitively increases the signal to noise ratio of neural information by adding an optimal level of noise (Moss et al, 2004 ). Chakravarthy ( 2013 ) suggested that the basal ganglia may facilitate willed actions using SR. High levels of synchronized neural activity in the STN and Globus Pallidus pars internus are neural correlates of PD, and so the underlying pathophysiology of PD may impair the basal ganglia’s ability to apply SR in facilitating movement. This also helps to explain why low frequency DBS pulse trains may worsen the motor signs of PD, and low amplitude random DBS pulses may have superior efficacy compared with traditional high frequency DBS pulse trains (Tass et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, SR counter-intuitively increases the signal to noise ratio of neural information by adding an optimal level of noise (Moss et al, 2004 ). Chakravarthy ( 2013 ) suggested that the basal ganglia may facilitate willed actions using SR. High levels of synchronized neural activity in the STN and Globus Pallidus pars internus are neural correlates of PD, and so the underlying pathophysiology of PD may impair the basal ganglia’s ability to apply SR in facilitating movement. This also helps to explain why low frequency DBS pulse trains may worsen the motor signs of PD, and low amplitude random DBS pulses may have superior efficacy compared with traditional high frequency DBS pulse trains (Tass et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…From a behavioural point of view, it would have been sufficient to include just one neural unit for each component to address the target experiment of McCairn and colleagues [ 49 ]. Indeed, this experiment involved monkeys not solving any specific task but rather producing motor tics as spontaneous input-free behaviors under neural noise (as detailed below, in the model such noise is intended to capture the spurious effects on neural activation due to the signals supplied by other cortices as well as the effect of intrinsic neural noise [ 77 – 80 ]). However, it was important to include a larger number of neural units to reproduce in a realistic way the circuitry implementing the competitive dynamics typical of some components of the model, in particular of the BG [ 21 , 81 ], relevant to the production of tics (see sections “The basal ganglia and their loops with the thalamo-cortical system: anatomy and physiology” and “The model predicts that the interplay between dopaminergic signal and cortical activity triggers the tic event”).…”
Section: Methodsmentioning
confidence: 99%
“…Based on the theory that STN-GPe chaotic dynamics are responsible for the generation of noise that is crucial for exploration (Chakravarthy et al, 2010 ; Kalva et al, 2012 ; Chakravarthy, 2013 ; Mandali et al, 2015 ) and which is no longer produced in PD condition, we can safely assume the presence of bursting and synchronous activity in STN. This pathological bursting activity leads to two outcomes; (1) Increase in the firing rate of GPi neurons leading to longer RT and (2) Regularized bursting STN activity that lead to a deterministic activation of the GPi neurons without any noise eventually leading to non-variable reaction time (no standard deviation).…”
Section: Resultsmentioning
confidence: 99%